Peer interactions, local markets, and wages: Evidence from Italy - Irene Brunetti; Valerio Intraligi; Andrea Ricci; Claudia Vittori (Global Labor Organization (GLO), 2023)
This paper investigates the relationship between the spatial distribution of occupations with a high content of peer interactions and wages among Italian provinces. At this aim, we use a unique employer-employee dataset obtained by merging administrative data on wages and labor market histories of individuals, with survey data on job tasks and contents. The spatial distribution of jobs intensive in peer-interactions is further measured according to the occupational structure of Italian provinces. The econometric analysis shows that the concentration of peer interactions leads to higher wages at the province level. These results are robust to firms and workers' heterogeneity and endogeneity issues.
Keywords: J31; R12; R23; 330; Peer interactions; Wages; Agglomeration externalities